Priority directions of the state support of the development of agro-industrial production of the Krasnodar territory under the conditions of the sanction regime - S. Y. Andreev; T. A. Bochkova; S. A. Mamiy (Новые технологии, 2019)
In a market economy activities of the subjects of the agro-industrial complex are influenced by a number of internal and external factors, which makes the adaptation of the system of state regulation of the agricultural sector of the economy relevant as the external environment, affecting the operating conditions of entrepreneurs in the agricultural sector changes. That determines the relevance of the research. In current conditions, there is a high need to clarify certain theoretical and methodological provisions, aspects of the identification of agrarian business entities; to improve the efficiency of the organizational and economic mechanism of state regulation of the activities of agrarian business entities, as well as to identify promising areas of state regulation of the development of the agro-industrial complex, taking into account regional characteristics of the development of the agrarian sector. The aim of the study is to develop practical recommendations for improving the effectiveness of state support for the subjects of the agro-industrial complex in the context of the sanction regime. The object of the study was the subjects of agribusiness in Krasnodar Territory. The purpose of the study is to determine the directions for stimulating the development of agribusiness in the region by replacing imports. The article sets forth recommendations on the formation of the organizational and economic mechanism for the implementation of a regional program for the import substitution of agricultural products in the Krasnodar Territory, aimed at stimulating the development of agrarian business entities in the region. An algorithm for the formation of the concept of import substitution of agricultural products and the order of formation of the target program of import substitution in the agricultural sector of the region has been presented. A flowchart of the proposed organizational and economic mechanism for the implementation of a regional program for the substitution of agricultural products in the territory of the region has been recommended for implementation.